Optimal irrigation and nitrogen fertilization for growth and yield of perennial ryegrass (Lolium perenne) - DUAN Kelong; NIU Zuirong; ZHANG Zhenrong; SONG Shuzhen; LI Miaoqi; GUO Sheng (Guan'gai paishui xuebao)
[Objective] Ryegrass (Lolium perenne) is extensively cultivated in Northwestern China for various purposes ranging from forage to landscaping. This paper presents the results of an experimental study on optimal irrigation and nitrogen fertilization for growth and yield of perennial ryegrass in managed grasslands in Yongdeng County in Gansu province, China. [Method] The field experiment consisted of two irrigation treatments by keeping the soil water content above 75%-85% (W1) or 55%-65% (W2) of the field capacity. Each irrigation treatment had three nitrogen treatments by applying 210 (N1), 180 (N2) and 150 kg/hm2 (N3) of nitrogen. In each treatment, we measured the growth traits, yield, and water and nitrogen use of the ryegrass at different growth stages. The optimal irrigation and nitrogen fertilization was determined by the entropy-weight TOPSIS model. [Result] Both irrigation and nitrogen significantly influenced ryegrass growth and yield. Increasing irrigation amount or nitrogen application improved growth traits and yield. However, nitrogen partial factor productivity (PFPN) decreased with increase in nitrogen application, and increasing irrigation amount reduced irrigation water use efficiency (IWUE). Nitrogen application had a greater impact on growth and yield of the ryegrass than irrigation. The W1N1 combination resulted in the highest plant height, chlorophyll content, and yield, while W2N1 produced the largest stem diameter. The W1N3 combination had the highest PFPN, and IWUE was greatest in W2N2. Entropy-weight TOPSIS analysis showed that W2N2 was optimal for ryegrass growth and yield in the study area. [Conclusion] Maintaining soil moisture above 55%-65% of the field capacity combined with 180 kg/hm2 of nitrogen fertilization is the optimal strategy for improving the growth and yield of perennial ryegrass in Yongdeng County, Gansu Province, China.